COMPARATIVE STUDY OF MACULAR HOLE (MH) SURGERY: INTERNAL LIMITING MEMBRANE FLAP TECHNIQUE VS. AMNIOTIC MEMBRANE GRAFT - Nida Khalid; Anusheh Khalid Waheed; Mustafa Khalid Waheed; Nouman Aleem; Amna Rizwan; Muhammad Ayub Khan (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Macular holes remain difficult to treat, despite advancements. Methodology: This study has a prospective cohort, comparative study design. The study lasted for 6 months. The study was conducted in the Mayo Hospital, Lahore. 20 patients were included in the study who had macular hole surgery, 10 in each group (ILM Flap and AMG). IBM SPSS 27 v. was used to analyse the data. An independent sample t-test was used to compare the means of two independent groups (ILM flap and AMG) on a continuous dependent variable (BCVA postoperative). Results: The mean age (Mean=65.85 years) with SD=5.95. Females formed a larger proportion of the sample (65%) than males (35%). The internal limiting membrane flap group had a significantly higher mean ETDRS score (Mean=64.84, SD=5.18) than the AMG (Mean=49.78, SD=3.05), p<0.001. 69.2% of study participants with poor satisfaction reported improved quality of life (QoL), compared to 28.6% in the high satisfaction group, with p =0.073. Conclusion: This comparative study demonstrates a significant difference between anatomical success and patient-reported outcomes in MH surgery. The unanticipated inverse association between satisfaction and perceived quality of life (QoL) improvement indicated that psychological variables and disappointed expectations may have a significant impact on postoperative experiences in addition to quantitative visual outcomes.